Simulation and study of hybrid energy storage system for microgrid - Saragih, Arga Roh Sahrijal (2016)
Hybrid Energy Storage System (HESS), comprising of batteries and ultracapacitors, is becoming increasingly important for micro grids. While batteries are characterized by low discharge current but higher operation time ranging from 1hour to 25 hours, ultracapacitors are used for heavy discharge current in short period of time usually in milliseconds to few seconds. Purpose of this project is to study the effect of highly fluctuating load demands and associated transients on the stability of HESS operation. During this project, the author models batteries, ultracapacitors along with converters to simulate the HESS in MATLAB. Due to time constraint, this report is strictly limited to evaluation of the stability of HESS between energy sources. The author will also design the control algorithm for dealing with highly fluctuating load demands. Stability of HESS can be evaluated based on optimum power allocation between different energy sources without adding stress on any of them.